THEME: CREATING LEARNER-CENTERED TEACHING. A SCIENTIFIC APPROACHES TO ENHANCING EDUCATIONAL OUTCOMES - Eshboyev Abdushukur Berdinazarovich (TADQIQOTLAR, 2025)
Abstract Learner-centered teaching (LCT) has emerged as a transformative approach in education that prioritizes the needs, interests, abilities, and active involvement of students in the learning process. This scientific article explores the theoretical foundations, principles, practical strategies, and challenges involved in implementing learner-centered teaching across diverse educational settings. Drawing upon constructivist learning theories, cognitive psychology, and pedagogical research, the study emphasizes the shift from traditional teacher-directed methods to student- empowered learning environments. The article concludes by offering recommendations for educators, institutions, and policymakers aiming to foster effective learner-centered practices.